2020
DOI: 10.1111/1742-6723.13530
|View full text |Cite
|
Sign up to set email alerts
|

Emergency department resuscitative thoracotomy at an adult major trauma centre: Outcomes following a training programme with standardised indications

Abstract: ObjectiveThe objective of this study was to report the procedural incidence and patient outcomes after the 2009 introduction of an institutional resuscitative thoracotomy (RT) programme. Emergency physicians, general surgeons and emergency nursing trauma team members were trained to perform RT on thoracic trauma patients with an unresponsive systolic blood pressure (SBP) <70 mmHg within 30 min of arrival, prior to cardiothoracic team back‐up.MethodsA retrospective cohort study was conducted on patients who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…“Few surgical emergencies present so great a diagnostic challenge or provide as great a therapeutic reward,” wrote Driscoll in 1973, whilst discussing cardiac chamber rupture in blunt trauma. Whilst Beck's triad is present in only one third of trauma cases of pericardial tamponade [6] , the bedside ultrasound has ameliorated previous diagnostic challenges [2] , [3] . Ultrasound sensitivity and specificity for pericardial effusion have been reported as 96% and 98% respectively when performed by emergency physicians [8] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…“Few surgical emergencies present so great a diagnostic challenge or provide as great a therapeutic reward,” wrote Driscoll in 1973, whilst discussing cardiac chamber rupture in blunt trauma. Whilst Beck's triad is present in only one third of trauma cases of pericardial tamponade [6] , the bedside ultrasound has ameliorated previous diagnostic challenges [2] , [3] . Ultrasound sensitivity and specificity for pericardial effusion have been reported as 96% and 98% respectively when performed by emergency physicians [8] .…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac chamber rupture is associated with a high mortality rate - mostly attributed to the resultant cardiac tamponade [1] . Successful management of acute cardiac tamponade requires a high degree of clinical suspicion with early diagnosis facilitated by ultrasonography linked to timely operative intervention [2] , [3] .…”
Section: Introductionmentioning
confidence: 99%
“…It is often performed in resuscitative thoracotomy and can be performed simultaneously to relieve cardiac tamponade, hemostasis for cardiac, great vessel, pulmonary, chest wall injuries, prevention of air embolism, and direct cardiac massage [1,15,16]. Non-surgeons with good training and experience can perform it [17]; however, thoracotomy is a highly invasive procedure because it creates a new injury of Abbreviated Injury Scale (AIS) score of 3 points or more. There is a risk of postoperative bleeding, hypothermia, vascular injuries, intercostal arteriovenous injury, and spinal artery injury.…”
Section: Resuscitative Thoracotomy With Aortic Cross-clampmentioning
confidence: 99%
“…3 Identify patients with the highest likelihood of benefitting from the procedure by assessing for cardiac tamponade with ultrasound. Local data from the Alfred Hospital Trauma Registry reveal that carefully selected blunt trauma patients who undergo an ED RT have a survival as high as 26% 4 and a recent European systematic review found an overall survival rate of 12.9% for ED RT performed for blunt trauma. 5 Shouldn't the thoracotomy be done in theatre?…”
Section: Surely Blunt Trauma Patients Should Not Have a Thoracotomy?mentioning
confidence: 99%